Hydromorphology of coastal zone and structure of watershed agro-food system are main determinants of coastal eutrophication. (11th February 2021) - Garnier, Josette; Billen, Gilles; Lassaletta, Luis; Vigiak, Olga; Nikolaidis, Nikolaos P; Grizzetti, Bruna
Abstract: For a number of well-documented watersheds and their adjacent coastal zones, a simplified, but generic approach was developed to explore current nutrient deliveries to their corresponding marine system, characterized by their flushing rate/residence time and morphology. An indicator of eutrophication was defined derived from both the C:N:P:Si stoichiometry of the riverine nutrient delivery and the physical features of the receiving marine bay (B_ICEP). Results show that the morphological and hydrological conditions characterizing coastal zones are the main determinants of the manifestation of eutrophication caused by an imbalance of nitrogen (and/or phosphorus) with respect to silica in the river nutrient loading. Action on the structure of the agro-food system of the upstream watershed, which determines the nitrogen losses to the hydrosystem, is identified as the most efficient control for attenuating coastal eutrophication. A comprehensive and generic concept of the systemic processes responsible for river and coastal water degradation can be achieved with a chain of nested models, describing the terrestrial agro-food system of the watershed, the river network, including the biogeochemical processes responsible for water quality, and the ecological functioning of the receiving marine area, in terms of carbon, nitrogen, phosphorus, and silica cycles. This leads to a land-to-sea continuum view, promoting interdisciplinarity and dialogue among the various scientific communities and their modeling approaches. This would also help the actors in multiple sectors (farming, fisheries, tourism, etc) and policy-makers make harmonized choices for a sustainable environment through an economically and socially viable way of life for all citizens.